Toxicity of leadership and its impact on employees: Exploring the dynamics of leadership in an academic setting - Baloyi, Gift T. (HTS teologiese studies, 2020)
Constructive leaders highlight elements of motivation to employees to grow in order to achieve goals for their institutions or departments. They do this either through understanding the significance of ethical leadership or servant leadership. However, people who work under toxic environments often have little or no choice but drop their energy levels and be completely demoralised because of the toxicity at their workplace. This includes stories of leaders who ridicule their employees in public, force employees to undergo physical and psychological pains, and promote divisiveness between colleagues. As the article focuses on leadership, and toxic leadership that is destructive not only for the workplace but also for human relationship, it argues for a need of ethical leadership which creates a dynamic relationship and trust between a leader and those led. The article concludes by stating that there is a relationship between ethical leadership and employee performance, and that this is very important for academic institutions.Contribution: Although the article reflects on the notion of leadership and its toxicity in an academic environment, the implications of the outcome are multidisciplinary, as ethical leadership is necessary in all human institutions (religion, politics, academia, corporate and social institutions or organisations).